An enhancement of world cloud algorithm used in worldle web application - Benitez, John Michael M. and Siggayo, Charlene Nicole U. 4 0 16; 5 (2015)
u
Undergraduate Thesis: (Bachelor of Science in Computer Studies major in Computer Science) Pamantasan ng Lungsod ng Maynila, 2015.
Keywords: 2 -- 0; 6; 20; 20; 2